Family Planning 2020 and Nepal’s Pledge - Amatya, Archana; Dangal, Ganesh (Journal of Nepal Health Research Council, 2017)
Family planning 2020 is a global partnership which hasbeen started after the 2012 London meeting on Familyplanning (FP) with the aim of improving the FP servicesto women and girls in the poorest countries.Achieving the FP2020 goal is critical to ensuring universal accessto sexual and reproductive health and rights by 2030 aspart of Sustainable Development Goals.